FACTORS INFLUENCING CASH HOLDING IN THE NON-CYCLICAL CONSUMER INDUSTRY AFTER THE COVID-19 PANDEMIC - Kurniawan, Viona; Bangun, Nurainun; Lukman, Hendro (Graduate Program of Universitas Tarumanagara, 2024)
The COVID-19 pandemic resulted in all sectors recording negative performance in the first quarter of 2020, including the consumer goods sector. In economic uncertainty due to the COVID-19 pandemic and intense competition between companies, many company experienced a significant decline and even decided to go on insolvency because they were unable to finance their operational activities. Therefore, the availability of cash or cash holding is essential to support the company’s operational activities, and error in calculating cash holding can result in the company experiencing financial difficulties. This study aims to analize the effect of cash conversion cycle, cash flow, and leverage on cash holding in consumer non-cyclicals companies listed on the Indonesia Stock Exchange (BEI) for the 2020-2022. The data used in this study were collected from IDX website. Analyzed data by using Eviews version 13. Sampling method used is Purposive sampling techniques. There were 47 companies met the criteria as the sample.